2009
DOI: 10.1111/j.1742-4658.2009.07378.x
|View full text |Cite
|
Sign up to set email alerts
|

Cholesterol oxidase: physiological functions

Abstract: An important aspect of catalysis performed by cholesterol oxidase (3β‐hydroxysteroid oxidase) concerns the nature of its association with the lipid bilayer that contains the sterol substrate. Efficient catalytic turnover is affected by the association of the protein with the membrane as well as the solubility of the substrate in the lipid bilayer. In this review, the binding of cholesterol oxidase to the lipid bilayer, its turnover of substrates presented in different physical environments, and how these condi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
61
1
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 78 publications
(67 citation statements)
references
References 102 publications
3
61
1
2
Order By: Relevance
“…These results contradict those of previous studies that showed that some microorganisms produce extracellular enzymes (e.g. cholesterol oxidase) to transform cholesterol (29). In addition, during oxic degradation of bile acids by the Gram-negative Pseudomonas sp.…”
Section: Journal Of Biological Chemistrycontrasting
confidence: 56%
See 1 more Smart Citation
“…These results contradict those of previous studies that showed that some microorganisms produce extracellular enzymes (e.g. cholesterol oxidase) to transform cholesterol (29). In addition, during oxic degradation of bile acids by the Gram-negative Pseudomonas sp.…”
Section: Journal Of Biological Chemistrycontrasting
confidence: 56%
“…Some cholesterol-transforming enzymes (e.g. FAD-containing cholesterol oxidase) are extracellular (29), implying that cholesterol can be transformed into other steroids before being imported by bacterial cells.…”
mentioning
confidence: 99%
“…In Streptomyces spp. and Rhodococcus equi, this step is catalyzed by cholesterol oxidases, which share 60% amino acid identity and have structures and mechanisms that are nearly identical (13,20). The closest M. tuberculosis homolog, Rv3409c, shares only 24% amino acid identity with the well-characterized cholesterol oxidases from Streptomyces and Rhodococcus.…”
mentioning
confidence: 99%
“…Atrat also speculated that steroid-transforming proteins, especially extracellular enzymes, such as cholesterol oxidase (3 -hydoxysteroid dehydrogenase), might make up part of the FMCM structure and stimulate sterols transport (Atrat, et al, 1991). Cholesterol oxidases are extracellular flavoenyzmes that catalyze the oxidation and isomerization of cholesterol to cholest-4-en-3-one (cholestenone or ketocholesterol), which is in charge of the first compulsory step in bacterial sterol catabolic pathways that transform sterols into sterones (Kreit & Sampson, 2009). These enzymes often occur in secreted and cell-surface-associated forms.…”
Section: Affinity Uptake Of Sterolsmentioning
confidence: 99%